Disrupting the status quo: a sustainability transitions analysis of the fashion system - Sophie Buchel; Aniek Hebinck; Mariangela Lavanga; Derk Loorbach (Sustainability: Science, Practice, & Policy, 2022)
The fashion industry has developed into a complex global system with persistent social and environmental sustainability challenges. Private, public, and civil society actors have condemned these persistent problems and called for system change toward sustainable fashion. While alternative practices and industry collaborations have emerged throughout the system, they have not added up to a sustainability transition. Instead, the system shows signs of being locked into unsustainability. The aim of this article is to examine the state of transition of the fashion industry through a multi-level perspective system analysis, based on a co-creative research project with the former C&A Foundation, which became the Laudes Foundation in 2020. This transition analysis shows that the fashion system is locked into a state of disconnection, uncontrollability, extraction, growth-focus, and disposability. We build from analysis and present a set of strategic transition pathways that can be pursued today throughout the fashion system to accelerate the transition to sustainable fashion.